Síntese e Caracterização da Matriz BaMoO4 e seus Compósitos (CaTiO3, BiCu3Ti3FeO12, Li2TiO3) para Aplicações em Componentes na Região de Micro-Ondas e Radiofrequência - Nobrega, Francisco Alekson Chaves (2023)
Some electroceramics can be used as electronic components in the wireless communication network. These stand out because they have the possibility of receiving and transmitting radiation at a certain frequency and can be used as a resonator antenna. One of the ceramics used as an antenna is calcium titanate (CaTiO3) which has a permittivity (e'r) above 150.00 at the 2.39 GHz frequency. However, its temperature coefficient at the resonant frequency (tf) is greater than 650.00 ppm/°C, a value outside the range of -10.00 to + 10.00 ppm/°C. In radiofrequency, CaTiO3 presents conductivity around 10−12 to 10−20/Sm and can be used as an electrical insulator. However, we seek to synthesize ceramic composites with tf values in the range of -10.00 to + 10.00 ppm/°C. With this, this work intends to synthesize barium molybdate (BaMoO4) and manufacture its composites both by solid-state reaction and that exhibit dielectric properties to be applied as resonator antennas and electrical insulators, also synthesize BaMoO4 by mechano-milling. The composites (1-x) BaMoO4 - (x) CaTiO3, (1-x) BaMoO4 – (x) BiCu3Ti3FeO12 and (1-x) Li2TiO3 – (x) BaMoO4 were synthesized in which the formation of their The phases was characterized by X-Ray diffraction. The synthesis of BaMoO4 by mechanosynthesis was also carried out at 6, 8, 10, and 12 h of milling. In the microwave region, all composites showed at least one sample with a tf value in the range of -10.00 to + 10.00 ppm/°C. In the antenna studies, the samples (1-x) BaMoO4 - (x) CaTiO3 showed efficiency above 75%, directivity above 4.40 dB and Gain above 3.93 dBi. In the radiofrequency evaluation by impedance spectroscopy, it was demonstrated that the BaMoO4 matrix and the composites presented thermally activated processes, with a decrease in activation energy (Ea) from 1.48 to 0.31 eV with the increase of CaTiO3 concentration in the matrix, as well the high permittivity value e'r = 13700 (in 1 Hz at 30 °C) of BaMoO4 stands out. It is concluded that the BaMoO4 composites can present samples with tf in the range of -10.00 to +10.00 ppm/°C, the (1-x) BaMoO4 - (x) CaTiO3 composites can be manufactured by the reaction of solid state with sintering at a temperature of 900 °C, and exhibit dielectric properties in the microwave and radio frequency region. And BaMoO4 can be synthesized by mechano-milling.